Case Report: When multiple system atrophy masquerades as CASPR2 autoimmune encephalopathy: a diagnostic pitfall - Zhang, Jun; Wang, Yueming; Chen, Le; Li, Jun (Frontiers in Human Neuroscience, 2025)
IntroductionMultiple system atrophy (MSA) is a sporadic, adult-onset neurodegenerative disorder characterized by rapid progression. Early diagnosis remains particularly challenging, especially when CASPR2 antibodies are detected during the early stages of disease progression.Case presentationA 56-year-old female presented with chronic progressive cerebellar ataxia. Serum analysis revealed the presence of CASPR2 antibodies. Brain MRI demonstrated atrophy of the brainstem and cerebellum. The external anal-sphincter electromyography (EAS-EMG) indicated autonomic nerve dysfunction in the absence of overt clinical symptoms. Despite treatment with high-dose corticosteroids and immunosuppressants, no clinical improvement was observed. During follow-up, symptoms of autonomic nerve dysfunction emerged, leading to a clinical established diagnosis of cerebellar subtype of multiple system atrophy (MSA-C).ConclusionIn the early stages of MSA, autonomic nerve dysfunction may not manifest clinically. Therefore, close follow-up is essential for accurate diagnosis. EAS-EMG exhibits high sensitivity in detecting subclinical autonomic dysfunction. Although the co-occurrence of MSA-C and high-titer (1:100) CASPR2-IgG is uncommon, this case highlights the critical importance of relying on the overall clinical presentation, rather than on isolated laboratory findings, to establish the primary diagnosis.